Electrode–Electrolyte Interfacial Chemistry Modulation for Ultra‐High Rate Sodium‐Ion Batteries. Issue 18 (9th March 2022) - Tang, Zheng; Wang, Hong; Wu, Peng‐Fei; Zhou, Si‐Yu; Huang, Yuan‐Cheng; Zhang, Rui; Sun, Dan; Tang, You‐Gen; Wang, Hai‐Yan
Abstract: Sodium‐ion batteries capable of operating at rate and temperature extremes are highly desirable, but elusive due to the dynamics and thermodynamics limitations. Herein, a strategy of electrode–electrolyte interfacial chemistry modulation is proposed. The commercial hard carbon demonstrates superior rate performance with 212 mAh g −1 at an ultra‐high current density of 5 A g −1 in the electrolyte with weak ion solvation/desolvation, which is much higher than those in common electrolytes (nearly no capacity in carbonate‐based electrolytes). Even at −20 °C, a high capacity of 175 mAh g −1 (74 % of its room‐temperature capacity) can be maintained at 2 A g −1 . Such an electrode retains 90 % of its initial capacity after 1000 cycles. As proven, weak ion solvation/desolvation of tetrahydrofuran greatly facilitates fast‐ion diffusion at the SEI/electrolyte interface and homogeneous SEI with well‐distributed NaF and organic components ensures fast Na + diffusion through the SEI layer and a stable interface. Abstract : In a THF‐based electrolyte with a weak solvation structure, Na + desolvation is fast and a uniform solid electrolyte interphase (SEI) with abundant NaF and organic compounds is generated on the commercial hard carbon anode. This greatly enhances the interface stability and enables the rapid migration of Na + in the SEI, thus realizing the high rate capability, long‐term stability and good low‐temperature performance for the hard carbon anode.